Low GILT Expression is Associated with Poor Patient Survival in Diffuse Large B-Cell Lymphoma - Phipps-Yonas, Hannah; Cui, Haiyan; Sebastiao, Noemi; Brunhoeber, Patrick S.; Haddock, Ellen; Deymier, Martin J.; Klapper, Wolfram; Lybarger, Lonnie; Roe, Denise; Hastings, Karen T. (Frontiers in Immunology, 2013)
The MHC class II-restricted antigen processing pathway presents antigenic peptides acquired in the endocytic route for the activation of CD4+ T cells. Multiple cancers express MHC class II, which may influence the anti-tumor immune response and patient outcome. Low MHC class II expression is associated with poor survival in diffuse large B-cell lymphoma (DLBCL), the most common form of aggressive non-Hodgkin lymphoma. Therefore, we investigated whether gamma-interferon-inducible lysosomal thiol reductase (GILT), an upstream component of the MHC class II-restricted antigen processing pathway that is not regulated by the transcription factor class II transactivator, may be important in DLBCL biology. GILT reduces protein disulfide bonds in the endocytic compartment, exposing additional epitopes for MHC class II binding and facilitating antigen presentation. In each of four independent gene expression profiling cohorts with a total of 585 DLBCL patients, low GILT expression was significantly associated with poor overall survival. In contrast, low expression of a classical MHC class II gene, HLA-DRA, was associated with poor survival in one of four cohorts. The association of low GILT expression with poor survival was independent of established clinical and molecular prognostic factors, the International Prognostic Index and the cell of origin classification, respectively. Immunohistochemical analysis of GILT expression in 96 DLBCL cases demonstrated variation in GILT protein expression within tumor cells which correlated strongly with GILT mRNA expression. These studies identify a novel association between GILT expression and clinical outcome in lymphoma. Our findings underscore the role of antigen processing in DLBCL and suggest that molecules targeting this pathway warrant investigation as potential therapeutics.